1982
DOI: 10.2527/jas1982.54182x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Lesions in Growing Swine Fed 3% Cement Kiln Dust as a Source of Calcium1

Abstract: Cement kiln dust (CKD) samples of which have been reported to stimulate growth in cattle and sheep, was fed to weanling pigs in a 42-d experiment. CKD at levels of 1.5 and 3.0% was added to a corn-soybean meal-oats-whey-type diet containing inadequate amounts of Ca (.4% of the diet) to provide final dietary Ca levels of .85 and 1.3%. A diet containing 3% limestone (1.3% dietary Ca) served as a positive control. Body weight gain was depressed by 3.0% CKD, and histopathological lesions of the humerus, not typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The observed lowered haemoglobin concentration and PCV and raised white cell and platelet counts suggest that cement dust exposure may have a deleterious effect on the bone marrow, the source of these cells. Indeed, severe bone lesions have been seen in weanling pigs fed cement kiln dust as a way of boosting dietary calcium (Pond et al, 1982). It may be interesting to further investigate this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed lowered haemoglobin concentration and PCV and raised white cell and platelet counts suggest that cement dust exposure may have a deleterious effect on the bone marrow, the source of these cells. Indeed, severe bone lesions have been seen in weanling pigs fed cement kiln dust as a way of boosting dietary calcium (Pond et al, 1982). It may be interesting to further investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we have hypothesized that such liver (Kanta et al, 1986) and bone (Pond et al, 1982) lesions observed following experimental exposure to cement dust in animals may occur in humans occupationally exposed to cement dust. Should this notion be correct, it is likely that parameters of liver and bone function in cement dust exposed subjects may be different from normal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Brockhaus et al (1981) and Dolgner et al (1983) reported that thallium containing atmospheric dust caused by emission of a cement plant affects the population living around the plant and subjects exhibited increased urinary thallium concentration as well increased thallium level in hair. It is important to note that the intercostal muscles might be equally affected on exposure of the subject with cement dust as already reported for lungs, heart, liver, spleen, bone and hair (Pimentel & Menezes 1978;Brockhaus et al 1981;Hogue et al 1981;Pond. et al 1982;Dolgner et al 1983;Reichrtova 1986;Maciejewska 1987).…”
mentioning
confidence: 85%
“…Maciejewska (1987) showed that the silica is deposited in the heart as well the spleen when introduced by intra-tracheal route and causes fibrosis. In addition, Pond et al (1982) added the cement kiln dust (CKD) in animal feed and found lesions of the humerus bone along with osteonecrosis, thinning of cortex and reduction of epiphyseal cartilage. In addition, Brockhaus et al (1981) and Dolgner et al (1983) reported that thallium containing atmospheric dust caused by emission of a cement plant affects the population living around the plant and subjects exhibited increased urinary thallium concentration as well increased thallium level in hair.…”
mentioning
confidence: 99%